RELATIONSHIP BETWEEN EMOTIONAL REGULATION STRATEGIES AND SELF –REPORTED EGO DEFENSE STYLES AMONG NURSING INTERNS AT ALEXANDRIA MAIN UNIVERSITY HOSPITAL - Amal Mohamed Hussein Shehata; Fatma Ramadan (Indian Journal of Psychiatric Nursing, 2017)
Internship year represents the first independent practice nurse graduates with the real work environment with all its challenges. The transition from student nurse to qualified staff nurse is often filled with overwhelming stress. Many nurse interns reported being distressed and emotionally overwhelmed in dealing with new or traumatic experiences when rotating various critical clinical settings. The experienced stress is likely to be exacerbated by lack of emotional regulation and adopting immature defenses that cause many forms of defensive behaviors. This study aimed to identify the relationship between emotional regulation strategies and self –reported ego defense styles among nursing interns at Alexandria Main University Hospital. Subjects of this study included 100 nursing interns in the internship year 2014-2015. Data was collected by using Defense Style Questionnaire 40’' (DSQ-40) and Emotion Regulation Questionnaire (ERQ). The finding showed that, mature defense style is positively correlated to cognitive reappraisal of emotional regulation, whereas, immature defense style was positively correlated to emotional suppression. A significant difference was noted between gender and emotional regulation strategies, female interns tend to use more cognitive reappraisal, whereas, male tend to use more emotional suppression.